Effect of intravenously injected killed pneumococci on leukocytes, complement, and phagocytosis in rabbits. - Reed, W P (1980)
A pneumococcal infection may be lethal in the absence of overwhelming pulmonary involvement, and death may occur even after the organisms have been killed with antibiotics. The mechanism of death is not understood but may be related to circulating pneumococcal products. For investigating the effects of nonviable pneumococci on several host defense mechanisms, rabbits were injected intravenously with 4 X 10(8) colony-forming units of killed sonified type 13 or type 29 pneumococci. Blood was sampled periodically for the next 24 h, and the following were measured: (i) circulating levels of leukocytes; (ii) activity of the classical and alternate complement pathways; and (iii) ability of the serum to opsonize pneumococci for ingestion and killing by polymorphonuclear leukocytes. Saline-injected control rabbits showed no change in any of the functions. Nonimmune rabbits injected with either pneumococcal serotype showed progressive and profound leukopenia, no change or an increase in classical and alternate complement pathway activity, and a profound reduction in the serum-opsonizing capcity for pneumococci of the same serotype as that used in the injection. The opsonizing capacity remained normal for the other serotype. When a previously immunized animal was injected, the opsonizing capacity for the homologous organism remained intact, but leukopenia nervertheless occurred.